IMPROVING THE PERFORMANCE OF SUSTAINABLE HUMAN RESOURCES IN COFFEE BEAN SUPPLY IN THE SATAK COFFEE AGROINDUSTRY, KEDIRI DISTRICT - Yunanto, yogi; Kristanti, Desi (STIE Mahardhika, 2024)
The supply of coffee beans in Indonesia involves several stakeholders, namely farmers, collectors and KUB (Joint Business Group). Sustainable supply activities are human, economic, social, environmental and technological resource management activities. The aim of this research is to analyze the sustainability performance of human resources in the supply of coffee beans in Indonesia. The data processing stage is identifying the supply of coffee beans in Indonesia. Analysis of identifying the supply of coffee beans in Indonesia, analysis of added value, measurement and assessment of the sustainable supply performance index for coffee beans. The added value of coffee bean supply was analyzed using the Hayami modification. SCOR-AHP (Supply Chain Operations Reference-Analytical Hierarchy Process) is used to measure the sustainability performance of human resources. The supply status of coffee beans is calculated using the Multi-Dimensional Scaling (MDS) technique with R software. The value added ratio for coffee farmers is low (46.58%) compared to collectors with (71.31%) and KUB (86.35% ). Farmers' supply performance is 71.99% lower than collectors with a value of 88.15% and KUB 86.77%. The economic dimension of sustainability is almost sustainable (78.39), the social dimension is sustainable (89.25), the environmental dimension is almost sustainable (79.63) and the technological dimension is almost sustainable (67.68). The aggregate value of sustainable supply shows 78.72% which means almost sustainable. This research recommends a strategy for building partnerships between coffee farmers and coffee cafes to improve performance and sustainability of the supply of coffee beans.